Analisis Strategi Pengembangan Bisnis dalam Optimalisasi Konektivitas Logistik pada PT Agung Logistik di Pelabuhan Patimban Subang Indonesia - Fatizhudin, Fatizhudin; Rudianto, Rudianto; Inkiriwang, Alfred; Pakpahan, Marisi (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to analyze the business development strategy implemented by PT Agung Logistic to optimize logistics connectivity at Patimban Port, Subang, Indonesia. With the development of Patimban Port as a national strategic project, supply chain efficiency and logistics system integration are crucial for industry players. The research methodology uses a qualitative approach with data collection techniques including in-depth interviews, observations, and documentation studies to formulate appropriate business strategy alternatives. The study's results indicate that PT Agung Logistic has a strong opportunity to strengthen its position by improving digital infrastructure, forming strategic partnerships, and using automation technology and logistics information system integration. Recommendations include developing multimodal services, optimizing distribution route management, and collaborating actively with port managers and local governments. This study serves as a strategic reference for PT Agung Logistic to increase competitiveness and operational efficiency in the Patimban Port logistics area.